The climate-smart agriculture implementer - CGIAR Research Program on Climate Change, Agriculture and Food Security; International Center for Tropical Agriculture (2015)
The rapid pace of climate change, and its impact on global food security, means a greater sense of urgency needs to be applied to putting adaption and mitigation measures in place. • Scientific experts and farmers in Asia face a communication gap which prevents the sustainable scaling out and adoption of climate-smart agricultural technologies and practices. • The CSA Implementer is a mobile phone application which uses crowdsourcing to bridge the communication gap between farmers and experts with the aim of fast-tracking CSA adoption.